2018
DOI: 10.1007/s40266-018-0584-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anticholinergic Drug Burden with Cognitive and Functional Decline Over Time in Older Inpatients: Results from the CRIME Project

Abstract: ACB and ARS have only a moderate degree of correlation. Use of drugs with anticholinergic properties in elderly patients is independently associated with cognitive and functional decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…However, the scale does not consider the dosage of an individual drug. Among older people, even a moderate change in the ARS score has been suggested to have an association with cognitive and functional decline (27); hence, we grouped the participants into four groups from none (G0) to very strong (G3) anticholinergic potential defined by the ARS to view also the participants with moderate anticholinergic burden. The ARS has been used in several studies particularly involving nursing home residents, and it has been shown to have an association with outcomes in cognitive performance and physical function (9,28,29).…”
Section: Methodsmentioning
confidence: 99%
“…However, the scale does not consider the dosage of an individual drug. Among older people, even a moderate change in the ARS score has been suggested to have an association with cognitive and functional decline (27); hence, we grouped the participants into four groups from none (G0) to very strong (G3) anticholinergic potential defined by the ARS to view also the participants with moderate anticholinergic burden. The ARS has been used in several studies particularly involving nursing home residents, and it has been shown to have an association with outcomes in cognitive performance and physical function (9,28,29).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, we observed a high ACB score in inpatients, and the role of cognitive decline on the development of ADEs needs further investigation [16]. Possible cofactors (such as age, education level, number of comorbidities, frailty and dementia) should be considered as a limitation of the study, acting as covariates in the correlation analysis (no adjustment was performed in the present study).…”
Section: Strengths and Weakness Of The Studymentioning
confidence: 70%
“…The information provided by INTERCheck ® includes drug interactions (database of interactions created and updated by the Mario Negri IRCCS Institute for Pharmacological Research); potentially inappropriate drugs in the elderly according to criteria from the scientific literature such as Beers and START (Screening Tool to Alert to Right Treatment)/STOPP (Screening Tool of Older Persons' Prescriptions); evaluation of the anticholinergic load (ACB scale); GerontoNet adverse drug reaction risk score algorithm (for identifying patients at greater risk of unwanted drug effects). In particular, the INTERCheck ® software describes the interactions between drugs according to their clinical relevance as "class A" (minor, no known clinical relevance), "class B" (moderate, interaction associated with an uncertain or variable event), "class C" (major, interaction associated with a serious event, but which can be managed, e.g., by reducing the dose) and "class D" (contraindicated or very serious, interaction associated with a serious event for which it is appropriate to avoid coadministration or to establish careful monitoring) [16]. The total INTERCheck ® score was considered as the sum of all obtained interactions.…”
Section: Assessmentsmentioning
confidence: 99%
“…As OAB might attribute to reduced bladder capacity, in the treatment for nocturia associated with OAB, anticholinergics are used as a standard therapy . However, anticholinergic therapy has several problems with a low adherence rate in continuing medication because of inadequate effectiveness and adverse drug reactions, such as dry mouth, constipation and cognitive impairment . Therefore, alternatives to anticholinergic drugs are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 However, anticholinergic therapy has several problems with a low adherence rate in continuing medication because of inadequate effectiveness and adverse drug reactions, such as dry mouth, constipation and cognitive impairment. [15][16][17][18] Therefore, alternatives to anticholinergic drugs are necessary. b 3 -Adrenoreceptors are predominantly expressed in human bladder tissue.…”
Section: Introductionmentioning
confidence: 99%